The societal unconscious : psychosocial perspectives on adult learning - Olesen, Henning Salling (Research on the education and learning of adults,, 2020)
"The Societal Unconscious presents an innovative development of theory and methodology for adult education and learning research, recognizing psychodynamic dimensions of learning processes. With few exceptions the unconscious has been neglected in critical adult education research. The psychosocial approach in this book seeks to re-integrate the societal and the psychodynamic dimensions in analyzing adult learners and learning processes. The book responds to contemporary awareness of the societal and cultural nature of subjectivity with a new material and dialectic psychosocial theory, comprising conscious as well as unconscious levels. Tracing interdisciplinary inspirations it sets a new broad horizon for in-depth understanding of learning in everyday life. A number of empirical analyses demonstrate the entanglement of societal and psychodynamic dimensions of learning. One part deals with the complex subjective continuities and discontinuities in individual learning and career. Another part comprises analyses of leadership and the social psychology of organizational processes, and the psycho-social aspects of institutional regeneration. A third part presents outlooks into the social psychology dimensions of wider societal and political processes, including "identity politics" and xenophobia"--